2015
DOI: 10.1159/000369962
|View full text |Cite
|
Sign up to set email alerts
|

Do Elderly Patients Call 911 When Presented with Clinical Scenarios Suggestive of Acute Stroke? A Cross-Sectional Study

Abstract: Background and Purpose: Among patients with acute stroke symptoms, delay in hospital admission is the main obstacle for the use of thrombolytic therapy and other interventions associated with decreased mortality and disability. The primary aim of this study was to assess whether an elderly clinical population correctly endorsed the response to call for emergency services when presented with signs and symptoms of stroke using a standardized questionnaire. Methods: We performed a cross-sectional study among elde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…This is similar to experiences described by stroke survivors in the UK [19]. Visual symptoms have been reported as the least known symptom of acute stroke [45,46]. Time from symptom to hospital treatment is crucial for stroke outcomes [47].…”
Section: Visual Problems As a Presenting Symptom Of Strokesupporting
confidence: 75%
“…This is similar to experiences described by stroke survivors in the UK [19]. Visual symptoms have been reported as the least known symptom of acute stroke [45,46]. Time from symptom to hospital treatment is crucial for stroke outcomes [47].…”
Section: Visual Problems As a Presenting Symptom Of Strokesupporting
confidence: 75%
“…Delayed arrival may be due to a lack of patient and public awareness of stroke symptoms, a decision to take a wait-and-see attitude, and a lack of proper immediate action [ 6 , 7 ]. More knowledge of stroke risk factors and stroke warning signs amongst patients is associated with an increased probability of correctly calling emergency services [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many stroke patients are still unable to arrive at the hospital within the golden time due to lack of knowledge on SWS [14]. Stroke awareness had a significant impact on early arrival at the hospital [2628], although some studies have found that previous stroke knowledge in patients was not associated with decision delay or EMS use [25,29]. Therefore, it should be emphasized to the general public not only to quickly recognize SWS by patients/bystanders, but also to contact the EMS immediately when stroke symptoms develop.…”
Section: Discussionmentioning
confidence: 99%